2021
DOI: 10.12669/pjms.38.1.4393
|View full text |Cite
|
Sign up to set email alerts
|

Significance of peritoneal washing cytology in the accurate staging of malignant ovarian tumors

Abstract: Objectives: To identify the percentage of ovarian cancers with positive peritoneal cytology and to correlate the positive cytology with the prognostic factors. Methods: This retrospective, cross-sectional study, evaluated the data of surgical specimens of malignant ovarian tumors, received in the Department of Pathology, Dow University of Health Sciences over a period of three years. The peritoneal cytology was correlated with these prognostic parameters: the size of the tumor, stage, capsular invasion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The absence of peritoneal cytology with the surgical specimen results in an incomplete staging of the ovarian cancers. The prognostic significance of malignant cells in washings or brushings varies, depending on the primary ovarian lesion, for example in serous borderline tumour or serous papillary carcinoma 20,21 . Moreover, positive washing cytology may be associated with adnexal involvement of endometrial carcinoma 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of peritoneal cytology with the surgical specimen results in an incomplete staging of the ovarian cancers. The prognostic significance of malignant cells in washings or brushings varies, depending on the primary ovarian lesion, for example in serous borderline tumour or serous papillary carcinoma 20,21 . Moreover, positive washing cytology may be associated with adnexal involvement of endometrial carcinoma 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic significance of malignant cells in washings or brushings varies, depending on the primary ovarian lesion, for example in serous borderline tumour or serous papillary carcinoma. 20,21 Moreover, positive washing cytology may be associated with adnexal involvement of endometrial carcinoma. 22 The significance of positive washings remains controversial for most types of uterine carcinoma, and staging for prognosis now requires histological confirmation of serosal/adnexal involvement.…”
Section: Tis Effusion Diagnostic Categoriesmentioning
confidence: 99%
“…Various studies have been conducted to determine the detection rate of peritoneal spread by peritoneal cytology that varied with various studies. Gulzar et al reported a cytology detection rate of 41.6%, Ozkara et al reported a rate of 62.2%, and Sanches and Matsubara reported a rate of 20% [ 21 - 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study was conducted in Pakistan by Gulzar et al on the significance of PWC for accurate staging of OCs. They found positive peritoneal cytology to be correlated to tumor stage [ 21 ]. A study was conducted by Yoshimura et al, in which 90 patients with OCs were examined.…”
Section: Discussionmentioning
confidence: 99%
“…Although full inspection of peritoneal cavity could not be achieved in three (9%) patients, peritoneal lavage could be performed in all patients. Peritoneal cytology (CY) has been used widely in the diagnosis and staging of various cancers, such as ovarian, and gastric cancer (15)(16)(17). Positive peritoneal cytology (CY+) in patients with PC is equivalent to metastatic disease and Stage IV according to the American Joint Committee on Cancer and the NCCN (18,19).…”
Section: Discussionmentioning
confidence: 99%